Autophagy in the immune system - Puleston, D; Simon, A (Wiley, 2014)
Autophagy is an intracellular homeostatic mechanism important for the degradation of waste components from the cytoplasm in acidic lysosomal compartments. Originally, surplus parts of the cytoplasm that acted as targets for autophagy were thought to comprise cellular organelles and proteins, but this has now extended to include a range of pathogens with particular emphasis on intracellular bacteria. The finding that autophagy can sequester intracellular bacteria and mediate their destruction has opened the door to a wider role for autophagy as an effector arm of the immune system. In innate immunity, autophagy works downstream of pattern recognition receptors where it facilitates a number of effector responses, including cytokine production and phagocytosis. Autophagy is also able to intersect pathways of innate and adaptive immunity through its potential to deliver antigens for antigen presentation. Autophagy provides a substantial source of antigens for loading onto MHC class II molecules and it may be important in dendritic cells for cross-priming to CD8(+) T cells. In lymphocytes, autophagy is essential for cell survival and homeostasis, particularly in T cells. In the thymus, autophagy can modulate the selection of certain CD4(+) T-cell clones while in the bone marrow autophagy is needed for B-cell development at specific stages. However, large holes exist in our knowledge as to how autophagy regulates, and is regulated by, the immune system and it is important to now apply what we have gleaned from in vitro studies to how autophagy operates in vivo in the setting of natural infection.